Women gathered around a maypole - Smith Bros.:::Creator::::::::::::
Two rings of women all dressed in the same costume with a wreath of flowers in their hair stand around a maypole. The inner ring hold the streamers on the maypole; the outer ring hold each others hands. There is a large unidentified building in the background